EXPERIENCES OF SOCIAL PARTICIPATION AND PLACE AMONG OLDER ADULTS LIVING IN URBAN NEIGHBOURHOODS IN THE UK AND BRAZIL. (11th November 2018) - Woolrych, R; Fisher, J; Lawthom, R; Sixsmith, J; Makita, M; Portella, A; Pereira, G; Murray, M
Abstract: Urban environments present opportunities and barriers in respect of social in/exclusion in old age. In response, policies and practices that support active ageing are increasingly being sought, central to which are the provision of opportunities for social participation. This paper presents qualitative data (including 180 face-to-face interviews, 120 walking interviews and 60 photo diaries), to examine experiences of social participation and place amongst older adults living across 6 cities and 18 neighbourhoods in the UK and Brazil. Thematic analysis identified key themes in relation to the urban environment and social participation: negotiating the built environment; place familiarity and control; place ownership and access; and security and safety. The findings support the integral role that urban environments play in shaping experiences of social participation in old age, identifying similarities and differences across case study areas. The paper offers suggestions for integrating social participation and place within age-friendly city frameworks.